(untitled) (Italian Journal of Public Health, 2011)
Background: The World Health Organization, the U.S. Centers for Disease Control and Prevention (CDC), and the Canadian Public Health Association have developed the Global Health Professions Student Survey (GHPSS) questionnaire in order to collect data on tobacco use and cessation counselling among health- profession students. The aims of the study were to evaluate the reliability and validity of the GHPSS questionnaire in Italy among health-profession students and to examine the prevalence of tobacco use, knowledge and attitudes to it and tobacco cessation training among students attending Italian medical schools using the standardised GHPSS approach. Methods: Before testing tobacco use prevalence, knowledge and attitudes, and tobacco cessation training, we calculated the Cronbach’s alpha to assess the internal validity with the intention of avoiding misleading results. The questionnaire was administered to 100 health-profession students and data were collected in March 2009, during regular class sessions among students of two Italian Schools of Medicine. The original GHPSS instrument was translated into the Italian language and modified by adding three specific questions regarding I) the knowledge about the use of antidepressants, ii) Acetylcholine Receptor Partial Agonists, and iii) counselling techniques used in tobacco cessation programs. Statistical analysis was performed using SPSS 13.0, statistical software for windows. Results: Cronbach’s alpha was higher on 17 items (alpha= 0.872), belonging to section I and IV (respectively: “Tobacco Use Prevalenceú and “Behaviour/Cessationú). The addition, also, of only one more of the others items (section)made the alpha value worse. Cronbach’s alpha for section VI for all items together (n. 44 items) was 0.815, which implies that the questionnaire had a very satisfactory internal validity. The prevalence of current smokers was 33%, while only 12% of students declared to be tobacco users. Interestingly, students who were tobacco users were 80% less likely to consider that health professionals needed training on smoking cessation techniques in comparison to non tobacco users. Conclusions: The questionnaire showed excellent reliability properties in the sample studied. In terms of internal consistency and validity, it appears to have an acceptable performance. Given the high prevalence of smokers among medical students, teaching them about the damages related to tobacco use, and how to help them quit smoking or tobacco use, emerged as important issues. Further studies to investigate these important issues, using a standardized method like GHPSS, are needed.